Éthique de deux libertins incarcérés : Mirabeau et Sade épistoliers - Rothé, Sophie (Lumen, 2021)
Mirabeau and Sade, who were incarcerated in the Castle of Vincennes in the same period for breaching moral standards, pursued a correspondence filled with ethical reflections from their time in prison. Their epistolary exchanges in jail show their interest in the penal reform initiated by Beccaria and carried out at the end of the eighteenth century. Their letters likewise underscore the incommensurable aspect of institutional power, the failures of the French judicial system, and the strategies used to crush prisoners. They denounce a world of inverted values in which duping the “deleter” becomes legitimate: the inmate becomes a victim of “brigands” and administrative “executioners.”